The Life of Syrian Asylum-Seeking Children in a Temporary Shelter Centre in Turkey: An Ethnographic Study on Primary School Education - Fansa, Mehmet; Ersoy, Ali (International Electronic Journal of Elementary Education, 2023)
This research aims to describe primary school children’s life and education experiences who escaped from the war environment in Syria and took refuge in Turkey. The study was conducted with an ethnographic research design. The study participants consisted of fourth-grade students, teachers, parents, and the close social circle of Syrian nationals who stayed in the temporary shelter in Turkey. Observation, interview, field notes, researcher’s diary, and ethnographic photograph were used to collect the research data. Content analysis was used in the analysis of the research data. As a result of data analysis, the lives of Syrian children and families in the temporary accommodation centre, before and after the asylum, the socio-economic life of the container city, and the daily life routines of the children in the camp are described. The research proposes to conduct more ethnographic research with children under temporary protection, describe their life stories and indigenous perspectives, organise events that will bring together local children and children in the shelter, and increase studies on teaching Turkish to foreigners.